A Contrastive Study of Lexical Semantics in English - Inchaurralde, Carlos (Armenian Folia Anglistika, 2005)
The article presents the initial generalizations of research in the fields of semantics and lexicography which are based on the examination carried out in 1962. Proceeding from the current results of the research, as well as the criteria elaborated in the fields of modern psycholinguistics and cognitive linguistics, the article puts forward the idea of the expansion of the lexical semantics in English and the existence of a basic semantic structure. The possibility of further similar researches with the inclusion of the Spanish vocabulary is also emphasized in the article.